Synthesis, Microstructure, Photocatalytic and Antibacterial Properties of ZnO-ZrO2 Nanocomposite - Jingjun YUAN; Xin YAO (Medžiagotyra)
Zinc oxide -Zirconium oxide (ZnO-ZrO2) nanocomposite (NC) was prepared using a sol-gel process. X-ray diffraction (XRD) studies showed the tetragonal and hexagonal structures of ZrO2 and ZnO respectively. FTIR studies indicated the Zn-O and Zr-O bonds in the prepared sample. The electron microscopy analysis showed the presence of crystalline materials with a uniform and compact structure. The optical studies showed a sharp absorption at about 400 nm and the Tauc plot evaluated the bandgap of 3.15 eV. The photodegradation performance of Methylene Blue (MB) dye was obtained for ZnO-ZrO2 NC using visible light irradiation and showed 96.89 % efficiency. The antibacterial activity of ZnO-ZrO2 NC against certain bacteria was investigated and the results indicated the significant antibacterial activity.